Organic chemistry - Clayden, Jonathan; Clayden, Jonathan; Warren, Stuart; Greeves, Nick (Oxford, Oxford university, 2012)
Organic Chemistry is a textbook that helps students in gaining a logical understanding of important concepts. It provides explanations on a vast variety of topics such as organic structure, structure of molecules, elimination reactions, stereochemistry, conformational analysis, etc.The book also explains various reactions and compounds to students. It makes use of clear diagrams of chemical structures in order to facilitate easier understanding. Each concept is explained with sufficient evidence, and reveals why certain compounds have certain reactions and how these reactions occur.Organic Chemistry helps students dispel any misconceptions that they may have about the subject, and also provides tips on how to avoid common mistakes. It explains the principles of the subject in a student-friendly manner. This second edition provides students numerous online resources for further study and reference.Questions and problems for each chapter helps students in practically applying what they had already learnt in theory. The chapters also contain boxes and margin notes which highlight key points about a particular concept. This paperback version was published by Oxford University Press in 2012. Key Features: The book contains updated material missing from the previous edition.The chapters have been rewritten and revised, with more emphasis on sound understating.This edition has cut down on clutter and taken out unnecessary details.
Figure acknowledgements 1182-1183p.; Periodic table of the element 1184-1186p.; Index 1187-1234p.
Keywords: Organic chemistry; Organic reactions; Organic structures; Chemistry